Filosofi dan Nilai-Nilai Dasar MSDM Islam: Studi Kasus Implementasi Di MIN 2 Batanghari - Jamilah, Jamilah; Repolinda, Repolinda; Ansori, Ansori; Yusup, Muhammad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Islamic human resource management (HRM) is fundamentally rooted in Qur’anic and Prophetic principles, viewing humans as khalifah fil ardh (vicegerents on earth) and ibadurrahman (servants of the Merciful) who embody core values of amanah (trustworthiness), ‘adl (justice), ihsan (excellence), syura (consultation), and rahmatan lil ‘alamin (mercy to all creation). This study explores the philosophy and foundational values of Islamic HRM through a qualitative descriptive case study at MIN 2 Batanghari, examining their implementation in daily operations, teacher development, and organizational culture. Employing semi-structured in-depth interviews with 10 key informants (principal, teachers, administrative staff), non-participant observations of workplace interactions and decision-making processes, and document analysis of school policies and performance records (2023–2025), the research reveals consistent application of these principles. The khalifah fil ardh concept fosters accountability and leadership at every level, while ibadurrahman shapes humble, patient, and socially oriented behavior. Amanah ensures integrity in task execution, ‘adl guarantees fair distribution of responsibilities and rewards, ihsan drives excellence in performance, syura promotes inclusive decision-making, and rahmatan lil ‘alamin manifests in social support programs and community engagement. The findings demonstrate that grounding HRM in these Islamic values strengthens ethical work culture, teacher morale, retention, and character education, while effectively addressing challenges such as limited resources through spiritual commitment and collective consultation. This research contributes empirical insights from a local madrasah ibtidaiyah negeri, filling a gap in contextual studies on Islamic HRM in Indonesian primary Islamic education.